El gran ausente: por un estatuto de la Oposición política tras 40 años de Constitución - Ruiz Ruiz, Juan José (Revista de Derecho Político, 2018)
Resumen: Dando por sentado que en un Estado plural y democrático como es el nuestro no puede haber más contrapeso para la mayoría que la minoría ni puede existir más contrapoder oponible a aquélla que la oposición. La ausencia de un estatuto constitucional para la oposición parlamentaria debiera ser una ceguera puede agudizar la desafección ciudadana en una época en la que los partidos mainstream con vocación de gobierno en la Unión Europea son «agents with two principals», es decir, agentes de dos instancias a veces contrapuestas, de un lado los electores, de otro las instituciones supranacionales, de modo que la brecha entre representantes y representados puede hacerse insalvable. Añádase a ello que la oposición parlamentaria post-crisis económica ya no se declina en singular sino que la fragmentación electoral ha multiplicado sus sujetos. Se impone por tanto como tarea futura la de proceder a una reconsideración e institucionalización de la oposición, No se trata con ello desde luego ni de instaurar un derecho a colegislar, o al obstruccionismo, o de atribuir poderes de veto, sino de reorientar la función de la oposición y dotarle de nuevos instrumentos, que pueden ir desde la revisión de las reglas de constitución de grupos parlamentarios, o la creación de la Oficina del Jefe de la oposición, al que se pueden reconocer facultades y derechos, la calendarización de los plenos de control, o la fijación del orden del día. Abstract: Assuming that in a plural and democratic state such as the Spanish one, there cannot be more counterbalance to majority than minority nor it can there be more counterbalance to the opposition than majority. The absence of a constitutional statute for the parliamentary opposition can become a blindness that could aggravates citizen disaffection at a time when the mainstream parties with a vocation for government in the European Union are «agents with two principals», that is, agents of two instances sometimes opposed, on one side the electors, on the other the supranational institutions, so that the gap between representatives and represented can become insurmountable. Furthermore, the post-economic crisis parliamentary opposition is no longer declined in singular but, because of electoral fragmentation it has multiplied its subjects. It is therefore necessary as a future task to proceed to a reconsideration and institutionalization of the opposition. The focus is not on establishing a right to co-legislate, or to obstructionism, or to attribute veto powers, but to reorient the function of the opposition and provide it with new instruments, which can range from the revision of the rules for the constitution of parliamentary groups, or the creation of the Office of the Chief of the opposition, to which faculties and rights can be recognized, the scheduling of plenary sessions of control, or fixing the order of bussiness. Summary: I. Foreword. II. Is there an opposition guarantee?: The difficulty in defining an statute for opposition. III. Being in the opposition, is it a constitutive fact or a declarative act? IV. The irrelevant character of the motion of censure. V. Bidirectional obstructionism of majority-opposition. 1. Over legislation. 2. Over the scrutiny function. 3. Over the investiture of the Government. VI. The role of constitutional conventions. VII. The prolongation of the political contest by means of appeals to the constitutional court and through the supportive media corporations. 1. Appeals to constitutional court. 2. Media corporations. VIII. Alternative forms to the parliamentary opposition: the experiences of constitutional opposition, extra-parliamentary opposition, vote-protest, strike and criminal prosecution. 1. The vote-protest. 2. The strike. 3. The criminal prosecution. IX. Balance and perspectives.